Method for identifying low-resistance hydrocarbon reservoir by porosity-resistivity-lithology matching relationship method - ZHAO JUNFENG; PENG TINGTING; REN HAIRONG; WANG LIANG; CHEN HANLIN; LI FENGQIN (2022)
The invention discloses a method for identifying a low-resistivity oil and gas reservoir through an in-layer porosity-resistivity-lithology matching relation method. The method comprises the steps that S1, in-layer lithology curve characteristics are analyzed; s2, analyzing intra-layer porosity curve characteristics; s3, analyzing the characteristics of the in-layer resistivity curve; s4, according to the in-layer porosity-resistivity-lithology matching relation, the reservoir fluid property is judged; and S5, verifying the property effect of the reservoir fluid. In the scheme, the identification of the low-resistance oil and gas reservoir is carried out through the matching relation among the in-layer porosity-resistivity-lithology curves, the erroneous judgment of the oil and gas reservoir can be avoided, the cost is not increased while the accuracy of logging identification of the oil and gas reservoir is improved, and the method is not only suitable for the evaluation of the low-resistance oil and gas res